Multifunctional Plasmonic Co-Doped Fe2O3@polydopamine-Au for Adsorption, Photocatalysis, and SERS-based Sensing - Xiong, W.; Zhao, Q.; Li, Xin Yong; Wang, L. (2016)
A new type of multifunctional plasmonic nanoparticles, cobalt-doped Fe2O3 at polydopamine-Au (Co-Fe2O3 at PDA-Au), is fabricated via coating PDA through self-polymerization onto Co-Fe2O3 and further loading gold nanoparticles by in situ reduction onto the surface of PDA shell. Benefiting from the universal adhesive ability of PDA and negative zeta potetntial of the composite, the Co-Fe2O3 at PDA-Au shows strong adsorptivity for cationic dyes. The presence of gold nanoparticle with the diameter of 15 nm in the Co-Fe2O3 at PDA-Au system promotes surface-enhanced Raman scattering (SERS) activity with an impressive detection limit of 1 × 10-6 m. Thanks to the synergistic effect of the light harvesting of PDA, the surface plasmon resonance of Au, and the electron conductibility of PDA and Au, the Co-Fe2O3 at PDA-Au exhibits an enhanced photocatalytic activity comparing with unmodified Co-Fe2O3. All the above-mentioned functions enable Co-Fe2O3 at PDA-Au to be a multifunctional material system for various applications toward environmental pollutants.